Gap reflecting film for photovoltaic module and preparation method of gap reflecting film
By using micro-nano indentation and wet etching processes on the aluminum-coated or silver-coated reflective layer of the photovoltaic module reflective film, the poor light reflection ability and low adhesion of the reflective film in the prior art are solved. The problem of this achieves efficient light reflection and improvement of light utilization.
Patent Information
- Application Number
- CN202411383364.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-02-07
AI Technical Summary
The light reflection ability of the existing photovoltaic module reflects the film at the welding tape is poor, which makes it difficult to effectively utilize the light energy, and the ultraviolet curing glue has low adhesion and poor coating effect, making pinholes prone to appear, reducing the light utilization rate.
Micro-nano indentation and wet etching technology are used to prepare strip-shaped triangular prism microstructures arranged in parallel and continuously on the aluminum-plated or silver-plated reflective layers to form a gap reflective film, avoiding the problem of low adhesion of ultraviolet glue, and through Direct etching of the reflective layer avoids the occurrence of pinholes.
The uniformity of the thickness of the reflective layer and the pinhole-free characteristics are achieved, the light reflection efficiency and light utilization of the photovoltaic module are improved, and the output power of the module is improved.
Smart Images

Figure CN119403301A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of reflective film materials, and in particular to a gap reflective film for a photovoltaic module and a preparation method thereof. Background Art
[0002] Photovoltaic modules achieve energy conversion by converting the light energy incident on the surface into electrical energy. Improving the utilization rate of light incident on the battery per unit area is of great significance to reducing light loss and increasing the output power of the module. At present, conventional photovoltaic modules are mainly composed of structures such as backplanes, batteries, and glass. Different battery cells are connected by welding strips, and the area of the welding strips is about 4% of the total area of the battery cells. Because the welding strips are mainly made by tin coating process, they have poor light reflection ability, so the light energy irradiated at the welding strips is difficult to be effectively utilized. Attaching a layer of film with high reflective performance to the welding strip to reflect the light back to the battery cell through the glass can effectively solve this problem. The Chinese patent (publication number CN208315576U) discloses a multi-level enhanced gain film for photovoltaic module string spacing, cell spacing and welding strips, which realizes light reuse by applying a reflective coating with a certain angle on the film.
[0003] The reflective film mentioned above is generally composed of four layers from bottom to top, namely, an adhesive layer, a substrate layer, a prism layer and a reflective layer. The prism layer is a micron-level prism structure, which is made by UV embossing; the reflective layer is located on the prism layer and is a metal material, which is made by magnetron sputtering, evaporation or electroplating. The structure of the above-mentioned reflective film is relatively complex, and the preparation of the reflective structure is often achieved through a two-step method: 1) a microstructure is formed by rolling on a substrate pre-coated with UV-curing glue using a customized mold with a specific complementary structure; 2) a reflective coating is then applied to the surface of the microstructure by magnetron sputtering or evaporation. There are two problems with this method. First, the adhesion between the UV-curing glue and the substrate layer is low, and the structure is easily damaged during actual use; second, the coating effect on the ridge of the microstructure is poor, and pinholes are easily formed, resulting in reduced light utilization. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a gap reflective film for photovoltaic modules and a preparation method thereof in view of the deficiencies in the above-mentioned prior art. In order to effectively improve the utilization efficiency of sunlight and increase the output power of the module, the present invention provides a gap reflective film with uniform reflective layer thickness and no pinholes based on micro-nano indentation and wet etching processes.
[0005] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: in the first aspect of the present invention, a gap reflective film for a photovoltaic module is provided, comprising a substrate layer, an adhesive layer located below the substrate layer, and a reflective layer located above the substrate layer, wherein a plurality of microstructures formed by embossing are arranged in an array on the reflective layer, wherein the microstructures are strip-shaped triangular prism structures which are continuously arranged parallel to each other, wherein the bottom surfaces of the strip-shaped triangular prism structures are connected in parallel to the surface of the reflective layer, and the top edges of the strip-shaped triangular prism structures protrude from the surface of the reflective layer.
[0006] Preferably, the longitudinal cross-section of the strip-shaped triangular prism structure is an isosceles triangle, the base length of the isosceles triangle is 20-40 μm, the height is 5-10 μm, and the vertex angle is 90°-150°.
[0007] Preferably, the reflective layer is made of aluminum or silver, has a thickness of 5 to 50 μm, and is made by one or more methods selected from vacuum evaporation, magnetron sputtering, and electroplating.
[0008] Preferably, the material of the substrate layer is one or more of polyethylene terephthalate (PET), polyvinylidene fluoride (PVDF), and polyimide (PI), and the thickness of the substrate layer is 30 to 80 μm.
[0009] Preferably, the material of the adhesive layer is one or more of ethylene-vinyl acetate copolymer (EVA), polyolefin elastomer (POE), and ethylene-ethyl acrylate (EEA), and the thickness of the adhesive layer is 25 to 90 μm.
[0010] A second aspect of the present invention provides a method for preparing the gap reflective film for photovoltaic modules as described above, comprising the following steps:
[0011] S1, pre-treating the substrate layer;
[0012] S2, applying a layer of metal aluminum or metal silver coating on the upper surface of the substrate by one or more methods selected from vacuum evaporation, magnetron sputtering and electroplating to form a reflective layer;
[0013] S3, preparing a microstructure on the reflective layer by micro-nano imprinting;
[0014] S4. Applying an adhesive layer on the lower surface of the substrate layer by lamination to obtain the gap reflective film for the photovoltaic module.
[0015] Preferably, the step S3 is specifically:
[0016] S3-1, spin coating ultraviolet photoresist on the surface of the reflective layer and baking;
[0017] S3-2, attaching a template with a strip-shaped triangular prism structure pattern copied thereon to the surface of the UV photoresist on the reflective layer, and removing the template after UV curing;
[0018] S3-3, treating the product obtained in step S3-2 with oxygen plasma, and then placing it in an etching solution for etching;
[0019] S3-4, the product obtained in step S3-2 is cleaned with plasma to remove the remaining photoresist and form a microstructure on the reflective layer.
[0020] Preferably, in step S3-1, the procedure of spin coating the ultraviolet photoresist is: spin coating at 400-700 rpm / min for 4-16 s, and spin coating at 2000-5000 rpm / min for 20-60 s;
[0021] In step S3-1, the baking temperature is 70-90°C and the baking time is 1-3 minutes.
[0022] Preferably, in step S3-2, UV curing is performed under an inert gas atmosphere, the gas pressure is 0.09-0.36 MPa, and the UV irradiation time is 2-8 min.
[0023] Preferably, in step S3-3, the plasma treatment time using oxygen is 30 to 80 seconds;
[0024] In step S3-3, the temperature of the etching process is 40-70° C., the etching time is 10-60 seconds, and the etching solution used is one or more solutions of phosphoric acid, hydrochloric acid, nitric acid, and acetic acid;
[0025] In step S3-4, the plasma cleaning time is 30 to 90 seconds.
[0026] The beneficial effects of the present invention are:
[0027] The present invention provides a gap reflective film for photovoltaic modules and a preparation method thereof. Different from the existing solution which uses a three-layer structure of substrate-microstructure layer-reflective layer to achieve reflection, the reflection function of the present invention is directly achieved through the substrate-reflective layer. The strip-shaped triangular prism microstructure is prepared by directly using an embossing-wet etching process on the aluminum-plated or silver-plated reflective layer, which can effectively avoid the problem of low adhesion between ultraviolet glue and the substrate.
[0028] The strip-shaped triangular prism microstructure of the present invention is directly obtained by etching on the aluminum-plated reflective layer, has no pinholes, and has higher reflection efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a schematic structural diagram of a gap reflective film for a photovoltaic module of the present invention;
[0030] Figure 2 This is the reflectivity curve of the gap reflective film for the photovoltaic module prepared in Example 1 in the visible light band. DETAILED DESCRIPTION
[0031] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.
[0032] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0033] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.
[0034] Reference Figure 1 The present invention provides a gap reflective film for a photovoltaic module, comprising a substrate layer, an adhesive layer located below the substrate layer, and a reflective layer located above the substrate layer, wherein a plurality of microstructures formed by embossing are arranged in an array on the reflective layer, wherein the microstructures are strip-shaped triangular prism structures that are continuously arranged parallel to each other, wherein the bottom surfaces of the strip-shaped triangular prism structures are connected in parallel to the surface of the reflective layer, and the top edges of the strip-shaped triangular prism structures protrude from the surface of the reflective layer.
[0035] In a preferred embodiment, the longitudinal cross-section of the strip-shaped triangular prism structure is an isosceles triangle, the base length of the isosceles triangle is 20 to 40 μm, more preferably 35 μm; the height is 5 to 10 μm, more preferably 8 μm; the vertex angle is 90° to 150°, more preferably 120°.
[0036] In a preferred embodiment, the reflective layer is made of aluminum or silver, and is produced by one or more methods selected from vacuum evaporation, magnetron sputtering and electroplating, with a thickness of 5 to 50 μm, more preferably 15 μm.
[0037] In a preferred embodiment, the material of the substrate layer is one or more of polyethylene terephthalate (PET), polyvinylidene fluoride (PVDF), and polyimide (PI).
[0038] In a preferred embodiment, the thickness of the substrate layer is 30-80 μm, more preferably 50 μm.
[0039] In a preferred embodiment, the material of the adhesive layer is one or more of ethylene-vinyl acetate copolymer (EVA), polyolefin elastomer (POE), and ethylene-ethyl acrylate (EEA).
[0040] In a preferred embodiment, the thickness of the adhesive layer is 25-90 μm, more preferably 40 μm.
[0041] The present invention also provides a method for preparing the above-mentioned gap reflective film for photovoltaic modules, comprising the following steps:
[0042] S1. Pre-treating the substrate layer; the pre-treatment method is plasma or primer to increase the adhesion of the substrate;
[0043] S2, applying a layer of metal aluminum or metal silver coating on the upper surface of the substrate by one or more methods selected from vacuum evaporation, magnetron sputtering and electroplating to form a reflective layer;
[0044] S3, preparing a microstructure on the reflective layer by micro-nano imprinting;
[0045] S4. Apply an adhesive layer on the lower surface of the substrate layer by laminating to obtain a gap reflective film for a photovoltaic module.
[0046] In a preferred embodiment, step S3 is specifically as follows:
[0047] S3-1, spin coating ultraviolet photoresist on the surface of the reflective layer and baking;
[0048] S3-2, attaching a template with a strip-shaped triangular prism structure pattern copied thereon to the surface of the UV photoresist on the reflective layer, and removing the template after UV curing;
[0049] S3-3, treating the product obtained in step S3-2 with oxygen plasma, and then placing it in an etching solution for etching;
[0050] S3-4, the product obtained in step S3-2 is cleaned with plasma to remove the remaining photoresist and form a microstructure on the reflective layer.
[0051] In a preferred embodiment, in step S3-1, the procedure for spin coating the ultraviolet photoresist is: spin coating at 400-700 rpm / min for 4-16 s, and spin coating at 2000-5000 rpm / min for 20-60 s; this spin coating procedure can obtain a photoresist layer with uniform thickness.
[0052] In a preferred embodiment, in step S3-1, the baking temperature is 70-90°C and the baking time is 1-3 minutes, in order to remove the organic solvent contained in the photoresist.
[0053] In a preferred embodiment, in step S3-2, UV curing is performed under an inert gas atmosphere, the inert gas is one or more of nitrogen, argon, and helium, the gas pressure is 0.09-0.36 MPa, and the UV irradiation time is 2 to 8 minutes.
[0054] In a preferred embodiment, in step S3-3, the temperature of the etching process is 40-70°C, more preferably 55°C; the etching time is 10-60s, more preferably 30s. The etching solution used is one or more solutions of phosphoric acid, hydrochloric acid, nitric acid, and acetic acid; the etching process is to obtain a triangular prism microstructure.
[0055] In a preferred embodiment, the plasma treatment time using oxygen is 30 to 80 seconds, more preferably 60 seconds, in order to remove the residual material and the photoresist at the bottom.
[0056] In a preferred embodiment, in step S3-4, the plasma cleaning time is 30 to 90 seconds, in order to remove the residual material and the photoresist at the bottom.
[0057] A multi-level enhanced gain film for photovoltaic module string spacing, sheet spacing and welding strips disclosed in a Chinese patent (publication number CN208315576U) is often prepared by a two-step method to achieve the reflective structure: 1) Rolling a microstructure on a substrate pre-coated with UV-curing glue by using a customized mold with a specific complementary structure; 2) Applying a reflective coating on the surface of the microstructure by magnetron sputtering or evaporation. There are two problems with this method. First, the adhesion between the UV-curing glue and the substrate layer is low, which is easy to cause structural damage during actual use; second, the coating effect on the ridge of the microstructure is poor, and pinholes are prone to appear, resulting in reduced light utilization.
[0058] Different from the above scheme, the present invention uses an imprint-wet etching process on the aluminum-plated reflective layer to prepare a triangular prism microstructure, which can effectively avoid the problem of low adhesion between the ultraviolet glue and the substrate; the microstructure of the present invention is obtained by etching directly on the aluminum-plated reflective layer, without pinholes, and has a higher reflection efficiency.
[0059] The above is the overall concept of the present invention, and detailed embodiments and comparative examples are provided below on the basis of the overall concept of the present invention to further illustrate the present invention.
[0060] Example 1
[0061] A gap reflective film for a photovoltaic module comprises a substrate layer, an adhesive layer located below the substrate layer and a reflective layer located above the substrate layer. A plurality of microstructures formed by embossing are arranged in an array on the reflective layer. The microstructures are strip-shaped triangular prism structures which are continuously arranged parallel to each other. The bottom surfaces of the strip-shaped triangular prism structures are connected in parallel to the surface of the reflective layer, and the top edges of the strip-shaped triangular prism structures protrude from the surface of the reflective layer.
[0062] The material of the substrate layer is polyethylene terephthalate (PET) and the thickness is 50 μm.
[0063] The material of the adhesive layer is ethylene-vinyl acetate copolymer (EVA) and the thickness is 40 μm.
[0064] The reflective layer is made of aluminum by vacuum evaporation and has a thickness of 15 μm.
[0065] The longitudinal section of the strip-shaped triangular prism structure is an isosceles triangle, and the base length of the isosceles triangle is 35 μm, the height is 8 μm, and the vertex angle is 120°.
[0066] The method for preparing the gap reflective film for the photovoltaic module comprises the following steps:
[0067] S1. Pre-treating the substrate layer by primer treatment to increase the adhesion of the substrate;
[0068] S2, applying a metal aluminum coating on the upper surface of the substrate by vacuum evaporation to form a reflective layer;
[0069] S3. Preparing microstructures on the reflective layer by micro-nano imprinting:
[0070] S3-1, spin-coating UV photoresist on the surface of the reflective layer, and baking at 80°C for 1.5 min; the procedure of spin-coating UV photoresist is: spin-coating at 550 rpm / min for 8 s, and spin-coating at 3600 rpm / min for 45 s;
[0071] S3-2, attaching a template with a strip-shaped triangular prism structure pattern to the surface of the UV photoresist on the reflective layer, and removing the template after UV curing; the UV curing process is carried out in a nitrogen atmosphere, with a pressure of 0.18 MPa, a time of 5 min, and a UV light source with a wavelength of 320 nm and a power of 600 W;
[0072] S3-3. The product obtained in step S3-2 is subjected to plasma treatment with oxygen for 70 seconds, and then placed in an etching solution for etching; the temperature during the etching process is 55°C and the etching time is 30 seconds; the etching solution is a mixture of phosphoric acid (80wt%), acetic acid (5wt%), nitric acid (5wt%) and deionized water (10wt%).
[0073] S3-4. Clean the product obtained in step S3-2 with a plasma cleaner for 70 seconds to remove the remaining photoresist and form a microstructure on the reflective layer.
[0074] S4. Apply an adhesive layer on the lower surface of the substrate layer by laminating to obtain a gap reflective film for a photovoltaic module.
[0075] Reference Figure 2 , is the reflectivity curve of the gap reflective film for the photovoltaic module prepared in this embodiment in the visible light band.
[0076] Example 2
[0077] The only difference between this example and Example 1 is that in this example, the thickness of the reflective layer is 30 μm.
[0078] Example 3
[0079] The only difference between this example and Example 1 is that in this example, the longitudinal section of the strip-shaped triangular prism structure is an isosceles triangle, and the base length of the isosceles triangle is 15 μm, the height is 5 μm, and the vertex angle is 100°.
[0080] Example 4
[0081] The only difference between this example and Example 1 is that in this example, the ultraviolet light curing time of step S3-2 is 3 minutes.
[0082] Example 5
[0083] The difference between this example and Example 1 is that in this example, the etching process temperature in step S3-3 is 40°C and the etching time is 50s.
[0084] Example 6
[0085] The only difference between this example and Example 1 is that in this example, the plasma cleaning time in step S3-4 is 30 seconds.
[0086] Comparative Example 1
[0087] The only difference between this example and Example 1 is that in this example, the thickness of the adhesive layer is 20 μm.
[0088] Comparative Example 2
[0089] The only difference between this example and Example 1 is that in this example, the substrate layer is not pretreated.
[0090] The gap reflective films for photovoltaic modules prepared in Examples 1-6 and Comparative Examples 1-2 were tested for structural reliability and light reflection performance:
[0091] Structural reliability is comprehensively evaluated by the surface appearance and coating uniformity of the reflective film, and the evaluation criteria are excellent > good > poor. Excellent means that the sample has a smooth surface at a medium viewing distance through the reflected light of a desk lamp, with less than 5 light transmission points per square meter, and the coating is uniform during the primer coating process without damage to the structure; good means that the number of light transmission points per square meter is greater than 5 and less than 20, and the primer coating process is uniform; poor means that the number of light transmission points per square meter is greater than 20, and there is a thickness difference in the primer.
[0092] The reflectance was measured using a UV-visible-near-infrared spectrophotometer.
[0093] The test results are shown in Table 1 below:
[0094] Table 1
[0095] sample Structural reliability Visible light reflectance range (%) Example 1 excellent 87.8~92.3 Example 2 good 86.3~90.1 Example 3 good 86.9~91.7 Example 4 excellent 85.1~90.2 Example 5 excellent 87.9~91.4 Example 6 excellent 88.5~90.8 Comparative Example 1 inferior 84.7~89.6 Comparative Example 2 inferior 84.9~89.5
[0096] According to the test results in Table 1, when the thickness of the bonding layer is too small (Comparative Example 1), the structural reliability will be reduced, but if the thickness of the bonding layer is too large, it is difficult to achieve uniform thickness during the coating process, so its thickness needs to be appropriate. When the thickness of the aluminum increases (Example 2), its bonding ability with the substrate becomes weaker and the structural stability is low; when the spacing and height of the triangular prisms become smaller (Example 3), the processing difficulty of the reflective film becomes greater; when the substrate is not pretreated (Comparative Example 2), the aluminum coating is prone to fine cracks during use. In addition, during the imprint wet etching process, the UV curing time, etching time and temperature, and temperature changes during plasma cleaning will affect the reflectivity of the embodiment.
[0097] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. A gap reflective film for a photovoltaic module, characterized in that: The invention comprises a substrate layer, an adhesive layer located below the substrate layer and a reflective layer located above the substrate layer, wherein a plurality of microstructures formed by embossing are arranged in an array on the reflective layer, wherein the microstructures are strip-shaped triangular prism structures which are continuously arranged parallel to each other, wherein the bottom surfaces of the strip-shaped triangular prism structures are connected in parallel to the surface of the reflective layer, and the top edges of the strip-shaped triangular prism structures protrude from the surface of the reflective layer.
2. The gap reflective film for photovoltaic modules according to claim 1, characterized in that: The longitudinal section of the strip-shaped triangular prism structure is an isosceles triangle, the base length of the isosceles triangle is 20-40 μm, the height is 5-10 μm, and the vertex angle is 90°-150°.
3. The gap reflective film for photovoltaic modules according to claim 1, characterized in that: The reflective layer is made of aluminum or silver, has a thickness of 5 to 50 μm, and is made by one or more methods selected from vacuum evaporation, magnetron sputtering and electroplating.
4. The gap reflective film for photovoltaic modules according to claim 1, characterized in that: The material of the substrate layer is one or more of polyethylene terephthalate, polyvinylidene fluoride, and polyimide, and the thickness of the substrate layer is 30 to 80 μm.
5. The gap reflective film for photovoltaic modules according to claim 1, characterized in that: The material of the bonding layer is one or more of ethylene-vinyl acetate copolymer, polyolefin elastomer, and ethylene-ethyl acrylate, and the thickness of the bonding layer is 25 to 90 μm.
6. A method for preparing a gap reflective film for a photovoltaic module according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, pre-treating the substrate layer; S2, applying a layer of metal aluminum or metal silver coating on the upper surface of the substrate by one or more methods selected from vacuum evaporation, magnetron sputtering and electroplating to form a reflective layer; S3, preparing a microstructure on the reflective layer by micro-nano imprinting; S4. Applying an adhesive layer on the lower surface of the substrate layer by lamination to obtain the gap reflective film for the photovoltaic module.
7. The method for preparing a gap reflective film for a photovoltaic module according to claim 6, characterized in that: Step S3 is specifically as follows: S3-1, spin coating ultraviolet photoresist on the surface of the reflective layer and baking; S3-2, attaching a template with a strip-shaped triangular prism structure pattern copied thereon to the surface of the UV photoresist on the reflective layer, and removing the template after UV curing; S3-3, treating the product obtained in step S3-2 with oxygen plasma, and then placing it in an etching solution for etching; S3-4, the product obtained in step S3-2 is cleaned with plasma to remove the remaining photoresist and form a microstructure on the reflective layer.
8. The method for preparing a gap reflective film for a photovoltaic module according to claim 7, characterized in that: In step S3-1, the procedure of spin coating the UV photoresist is: spin coating at 400-700 rpm / min for 4-16 s, and spin coating at 2000-5000 rpm / min for 20-60 s; In step S3-1, the baking temperature is 70-90°C and the baking time is 1-3 minutes.
9. The method for preparing a gap reflective film for a photovoltaic module according to claim 7, characterized in that: In step S3-2, UV curing is performed in an inert gas atmosphere, the gas pressure is 0.09-0.36 MPa, and the UV irradiation time is 2-8 min.
10. The method for preparing a gap reflective film for a photovoltaic module according to claim 7, characterized in that: In step S3-3, the plasma treatment time using oxygen is 30 to 80 seconds; In step S3-3, the temperature of the etching process is 40-70° C., the etching time is 10-60 seconds, and the etching solution used is one or more solutions of phosphoric acid, hydrochloric acid, nitric acid, and acetic acid; In step S3-4, the plasma cleaning time is 30 to 90 seconds.
Citation Information
Patent Citations
A multistage reinforcing gain membrane that is used for photovoltaic module cluster interval, piece interval and welds area
CN208315576U